2011
DOI: 10.5005/jp-journals-10011-1123
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Sex by Discriminant Function Analysis of Lateral Radiographic Cephalometry

Abstract: Objective: The present study is an attempt to develop a method to determine sex from the skull with lateral cephalometric radiograph using discriminant function analysis. Study design:The superciliary ridges, frontal sinuses, sella, cranial base and mastoid process were adopted as objects of lateral radiographic cephalometric measurements. The present study included cephalometric radiographs of 100 Indian adults chosen randomly from the records, each cephalometric radiograph was traced and nine linear and five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…in their study on 100 individuals found that it provided a greater degree of accuracy in determining the sex. [9] Devang Divakar et al . did a discriminate function analysis on a lateral cephalogram and found it as a reliable tool in determining the sex of an individual.…”
Section: Introductionmentioning
confidence: 99%
“…in their study on 100 individuals found that it provided a greater degree of accuracy in determining the sex. [9] Devang Divakar et al . did a discriminate function analysis on a lateral cephalogram and found it as a reliable tool in determining the sex of an individual.…”
Section: Introductionmentioning
confidence: 99%
“…The precision of determination rely upon the features that are present on the skull and their condition (Devang Divakar et al, 2015, Badam et al, 2011, Kamath et al, 2015, Wankhede et al, 2015). The veracity of determination of gender by means of pelvic bone alone, stated to be 90–100% accurate, which in turn made it as the most chosen bone for gender identification (Badam et al, 2011). Next to pelvis other skeletal elements which show near accurate results are the skull, thorax, vertebrae, femur and scapula (Devang Divakar et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6]9,10,15,16 The quantitative method was used in the present study to determine sex. Some authors have considered that this method is more reliable when pre-established points are used and have accepted that qualitative method are subjective and unsafe.…”
Section: Discussionmentioning
confidence: 99%
“…For example, prominences, bone crests and other anatomical abnormalities are more perceptible in male skulls than in female skulls. 2,4,5,9,[16][17][18][19] However, according to Badam et al, 9 Patil & Mody, 3 Shearer et al 13 and Spradley & Jantz, 1 metric analysis makes it possible to obtain results that are more objective, especially for researchers with little experience of determining individuals' sex. Moreover, this facilitates the statistical analysis on the sample and comparison with other studies.…”
Section: -611mentioning
confidence: 99%
See 1 more Smart Citation